A maquinaria do curso técnico em vestuário dos institutos federais da Região Sul, um estudo a partir da experiência das mulheres estudantes - Castro, Beatriz Helena Viana (2021)
This research is part of the line of research Theories and Cultures in Education of the Graduate Program of the Pontifical Catholic University of Rio Grande do Sul (PUCRS) and was carried out at the Federal Institutes of Education, Science and Technology. Federal Institutes are institutions that offer professional and technological education and are characterized by the strong presence of technology in their courses. This study analyzes the ways in which women relate to these technologies, when they enter a technical course. Women are holders of little-valued knowledge and are largely excluded from technological knowledge, hence the importance of trying to understand this reality from feminist readings, considering their experiences. The course analyzed was the Technical Course in Clothing and the research was carried out at three Federal Institutes in the southern region of Brazil. The chosen course composes the researcher's professional experience and the research question was: how do the students understand and access the technologies in the Technical Courses in Clothing of the IFs in the southern region of Brazil? The socioeconomic realities of the students who agreed to participate in the research were studied and the issues of class, race, gender and generation were considered. The methodological path was guided by guidelines on discussion groups, and the first step was the application of a questionnaire with closed questions to students regularly enrolled in the courses to learn about their characteristics, regarding class, race and age group. The closed questions helped in the elaboration of the students' socioeconomic panorama and also made it possible to know a little of their stories through their previous school experiences. The second stage was through discussion groups. And, once the transcriptions were made, we proceeded to the formulated and reflected interpretation of the discussion groups that generated the specific points of analysis. The third stage was the reading of the curricula of the courses, when a dialogue was established between the curriculum construction and the maintenance of power relations related to gender that appear, or are hidden, in it. The considerations of this thesis are that, despite the pandemic of COVID-19, this research identifies the concept of “specificity” as one of the findings to be maintained for gender and feminist studies in the context of technological training and training in a general, because, to a large extent, women still need to think about their formative experiences with their professions. The study does not end all learning possibilities, but opens the way for new debates and other perspectives.